Geology and petrology of Archean rocks in Guinea: a regional contribution to the knowledge of continental crust formation - (:unkn) unknown (My University, 2005)
The formation of the continental crust is one of the main topics of geosciences and, in this debate, the geologist plays a major role allowing the knowledge of the composition of the Earth surface and timing of the events responsible for the building of the crust. Once achieved the space and time framework of a given " piece " of continental crust, the main problems concern both the processes by which the crustal matter is created and those by which this matter differentiates, which may include chemical (magmatism, hydorthermalism) and physical (déformation, metamorphism) processes. This memoir is an attempt to reconstruct the mechanisms reponsible for the building and differentiation of the Archean crust of the south-western part of W-Africa from the data collected during different mapping projects of the BRGM in eastern and centre Guinea (south-east Guinea, 1998-1999 ; north-east Guinea, 1998-1999 ; centre Guinea, 2001-2003). My approach is essentially magmatologic with the aim of deciphering the origin of magmas and their mechanisms of differentiation. For this aim, the method used is mainly systematic and based on a comparison between the geochemical signatures of Archean rocks and those of recent rocks, as well as on a measure of the trace element fractionation of the sources of Archean magmas relative to a primordial mantle and to the sources of recent magmas. In the south-western part of W-Africa, the formation and differentiation of the Archean craton (the Kénéma-Man domain) has resulted from four major stages : 1/ Paleoarchean (~ 3.5 Ga) ; 2/ Leonean (~ 3.1-2.95 Ga) ; 3/ Liberian (~ 2.9-2.8 Ga) ; 4/ Late-eburnean (~ 2.1-2 Ga). The Paleoarchean stage is marked by the emplacement of moderately potassic granitoids with the common geochemical signatures of magmas derived from the high-P melting of subducted basic materials (" slab melts "). A the same time, basic rocks were actually subducted, eclogitised and stored in the subcontinental mantle
Keywords: African Research